Fully sustainable and high-performance fish gelatin-based triboelectric nanogenerator for wearable movement sensing and human-machine interaction. (November 2021) - Sun, Qizeng; Wang, Li; Yue, Xiaoping; Zhang, Linrong; Ren, Guozhang; Li, Donghai; Wang, Hongchen; Han, Yaojie; Xiao, Lulu; Lu, Gang; Yu, Hai-Dong; Huang, Wei
Abstract: Triboelectric nanogenerators (TENGs) have been demonstrated promising as flexible, portable, and wearable devices in energy harvesting and self-powered sensing, providing a new possibility in wearable electronics and human-machine interaction. To reduce the environmental pollution, many sustainable and natural materials have been applied as friction materials in TENGs; however, it is still challenging to fabricate fully sustainable and high-performance TENGs, possibly due to the difficulty in choosing suitable sustainable friction pairs. Herein, we develop a general method to fabricate a flexible, transparent, fully sustainable, and high-performance fish gelatin-based TENG with its friction layers all composed of the fish gelatin films prepared from kitchen waste fish scales. These films can degrade completely within 30 days in the soil. Modifying the two friction layers with dopamine and fluorinated silane respectively to serve as a promising triboelectric pair, the obtained TENG shows remarkable output performances, which could be further enhanced via surface structuralization and dimension optimization. An open circuit voltage of 500 V and a short circuit current of 4 μA are realized, and the power density reaches up to 100 μW cm −2 . To the best of our knowledge, the output voltage is much higher than that of the reported sustainable TENGs. Our fully sustainable TENG can directly light up 300 light-emitting diodes. Moreover, the device is also used in self-powered wearable sensing of human movements and in human-machine interaction. Our work demonstrates the great potential of utilizing the cost-efficient and sustainable fish scales in flexible, green, and wearable electronics, particularly in human-machine interaction. Graphical Abstract: In this work, we develop a simple and versatile method to fabricate a flexible, transparent, fully sustainable, and high-performance fish gelatin-based TENG with its friction layers all composed of the fish gelatin films prepared from kitchen waste fish scales. Our TENG is used in self-powered wearable sensing of human movements and in human-machine interaction. Our work demonstrates the great potential of utilizing the cost-efficient and sustainable fish scales in flexible, green, and wearable electronics, particularly in human-machine interaction. ga1 Highlights: A general method is developed to fabricate a flexible, transparent, fully sustainable, and high-performance TENG. The friction layers of the TENG are all composed of the fish gelatin films prepared from kitchen waste fish scales. The obtained fully sustainable TENG shows remarkable output performances, and the output voltage reaches 500 V. Our TENG demonstrates a great potential in green and wearable electronics, as well as in human-machine interaction.